Media Kerjasama Guru PAI dan Orang Tua dalam Membentuk Sikap Multikultural Siswa di SMP Muhammadiyah 48 Medan - Siti Zahra; Meyniar Albina (Kamaya: Jurnal Ilmu Agama, 2025)
This study aims to explore the role of collaborative media between Islamic Education (PAI) teachers and parents in shaping students’ multicultural attitudes at SMP Muhammadiyah 48 Medan. The study is based on the importance of multicultural education in fostering tolerance, appreciation of diversity, and mutual respect among students. The research employed a qualitative case study design. Data were collected through observations, interviews with PAI teachers, students, and parents, questionnaires, and documentation, and were validated using source triangulation. Data analysis was conducted descriptively to illustrate the role of collaborative media in developing students’ multicultural attitudes. The results show that media such as class WhatsApp groups, regular teacher-parent meetings, and active communication are effective in enhancing interaction and students’ understanding. Supporting factors include school principal support, parents’ readiness, and ease of communication, while constraints involve limited time and technical obstacles. This synergy effectively increases students’ awareness of tolerance, appreciation of cultural and religious diversity, and social skills that promote mutual respect. In conclusion, consistent collaboration between PAI teachers and parents through communication media plays a crucial role in shaping students’ multicultural attitudes. Support from all stakeholders and the effective use of media are key to the success of multicultural education in schools.